Efektivitas Daya Simpan dan Uji Organoleptik Nugget Ikan Gabus - Ester Rumaseb; Berliana Tampubolon; Guruh Suprayitno (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The problem of malnutrition in Papua is caused by economic factors and parents' limited knowledge about nutrition. The impact of malnutrition on children under five causes growth and development to be hampered and can interfere with productivity. Providing food with high protein is an alternative to improve the nutritional status of children under five with infectious disease problems. One of the foods that contains high protein and albumin which is a local food and is easy to obtain in the Papua region is snakehead fish. Objective: To determine the effectiveness of storage and organoleptic tests on snakehead fish nuggets. Methods The research design used in this study used the factorial analysis method. The research design used in this study used the factorial analysis method by comparing the four treatments with three repetitions for each treatment. The four treatments are looking for processing results without using preservatives stored in open spaces and in refrigerators and processing results using preservatives stored in open spaces and in refrigerators. In each treatment three repetitions were carried out to obtain valid conclusions, namely the 1st test (first day), 2nd test (third day) and 3rd test (fifth day). The data analysis used was the mean comparison between treatments without preservatives in the open space and in the refrigerator and using preservatives in the open space and in the refrigerator. The significance test used the Kruskall Wallis test followed by the Friedman test. Results: The difference test for snakehead fish nuggets without preservatives showed a significant difference compared to fish nuggets without preservatives with a p value <0.05. Conclusion: The most optimal storage time for cork fish nuggets without preservatives or with preservatives in an open space or normal temperature can last up to the 3rd day.